Factors Influencing Community Utilization of Public Toilets in Aek Kota Batu Village - Yulia Irma Ulina; Ayi Darmana; Nur’aini (PT Yapindo Jaya Abadi, 2025)
Feces are one of the waste products that lead to several issues in the medical field and act as a breeding ground for bacteria, thus their disposal requires extra care. Many individuals still do not use latrines, according to the first survey that researchers did in Batu City's Aek Puskesmas working region. Analyzing the variables influencing latrine use in the Aek City Health Center's Work Area in Batu was the aim of this study. This kind of research was carried out between October and November 2019 and used a cross-sectional study design and analytical survey. All household heads without a separate restroom made up the study's population. Purposive sampling was used in this study to establish the sample size, which consisted of 71 households. The data were analyzed using the logistic regression test formula for multivariate analysis, the chi-square formula for bivariate analysis, and univariate analysis. According to the study's findings, health workers' expertise, attitudes, and information have an impact on how often people use the public restrooms in Aek Kota Batu Village in 2019. In Aek Kota Batu Village in 2019, the information provided by health officers was the most significant factor preventing the population from using public restrooms. As a result, it is advised that residents of Desa Aek Kota Batu have access to public restrooms for proper bowel movements. Keywords: Knowledge, Attitudes, Information of Health Officers, Utilization of Latrines